Activation of NF‐κB after chronic ethanol intake and haemorrhagic shock/resuscitation in mice. (17th September 2013) - Maraslioglu, M; Weber, R; Korff, S; Blattner, C; Nauck, C; Henrich, D; Jobin, C; Marzi, I; Lehnert, M
Abstract : Background and Purpose: Chronic ethanol abuse and haemorrhagic shock are major causes of global mortality and, separately, induce profound hepato‐ and immune‐toxic effects via activation of NF‐κB. Here, we assessed the effects of chronic ethanol intake upon the pathophysiological derangements after haemorrhagic shock with subsequent resuscitation (H/R), with particular attention to the contribution of NF‐κB. Experimental Approach: Transgenic NF‐κB EGFP mice, expressing the enhanced green fluorescent protein (EGFP) under the transcriptional control of NF‐κB cis‐elements were fed a Lieber‐DeCarli diet containing ethanol (EtOH‐diet) or an isocaloric control diet for 4 weeks and were then pairwise subjected to H/R. Liver tissues and peripheral blood were sampled at 2 or 24 h after H/R. Cytokines in blood and tissue and leukocyte activation (as CD11b expression) were measured, along with EGFP as a marker of NF‐κB activation. Key Results: The EtOH‐diet increased mortality at 24 h after H/R and elevated liver injury, associated with an up‐regulation of NF‐κB‐dependent genes and IL‐6 release; it also increased production of NF‐κB‐driven intercellular adhesion molecule 1 (ICAM‐1) and EGFP in liver tissue. At 2h after the H/R procedure in ethanol‐fed mice we observed the highest proportion of NF‐κB activated non‐parenchymal cells and an NF‐κB‐dependent increase in polymorphonuclear leukocyte CD11b expression. Conclusions and Implications: The EtOH‐diet exacerbated liver injury after H/R, accompanying an overwhelming hepatic and systemic immune response. Our findings contribute to evidence implicating NF‐κB as a key player in the orchestration of the immune response in haemorrhagic shock patients with a history of chronic ethanol abuse.